Changes in occlusal vertical dimension in microwave processing of complete dentures. - Barbosa, Débora Barros; Compagnoni, Marco Antonio [UNESP]; Leles, Cláudio Rodrigues (FapUNIFESP (SciELO), 2002)
This study investigated the effect of different microwave curing cycles on the changes in occlusal vertical dimension of complete dentures. Four test groups with 12 maxillary dentures each were evaluated. Groups 1, 2 and 3 were polymerized with different cycles by microwave radiation and Group 4 was the control and cured by water bath. The average pin opening for all groups was less than 0.5 mm. There was no significant difference between the groups polymerized by the microwave method and the control group. However, analyses of the vertical dimension changes showed statistically significant differences between groups 2 (0.276 +/- 0.141 mm) and 3 (0.496 +/- 0.220 mm).
Keywords: acrylic acid resin; polymer; analysis of variance; chemistry; comparative study; denture; human; methodology; microwave radiation; nonparametric test; tooth occlusion; Acrylic Resins; Analysis of Variance; Denture Bases; Denture Design; Denture, Complete, Upper; Humans; Microwaves; Polymers; Statistics, Nonparametric; Vertical Dimension